Meningitis due to Streptococcus suis in Two Patients with Occupational Exposure from Northeastern Brazil - Francisco Breno Ponte de Matos; Luís Arthur Brasil Gadelha Farias; Camila Negreiro Dias; Lorena Pinho Mendes; Pedro Pinheiro de Negreiros Bessa (Case Reports in Infectious Diseases)
Streptococcus suis is an emerging zoonotic agent that causes bacterial meningitis. S. suis is an encapsulated Gram-positive, facultative anaerobic bacterium. This infection usually manifests in humans as meningitis, endocarditis, septicemia, and/or arthritis. The primary groups at risk for S. suis infection are individuals occupationally exposed to pigs and/or pork, for example, farmers, butchers, and hunters. Herein, we report two cases of meningitis related to S. suis with occupational exposure from the Ceará state, northeastern Brazil.